Analisis Kinerja Turbin Angin Savonius Dengan Profil Sudu U, Sudu Helix Tanpa End Plate Dan Menggunakan End Plate - Mitra Hari Ramadhan; Muhammad Firman; Heri Irawan (Journal of Mechanical Engineering and Applied Technology, 2026)
This study aims to analyze the performance of a Savonius-type wind turbine through variations in blade profile and the addition of an end plate. Experimental testing was conducted using a wind tunnel across three configurations: Model A (U-profile), Model B (helical profile without end plate), and Model C (helical profile with end plate). Wind speed was varied at 3.0 m/s, 4.0 m/s, and 5.0 m/s to evaluate turbine performance, including rotor rotational speed, torque, mechanical power, Tip Speed Ratio (TSR), and power coefficient (Cp). The results demonstrate that blade geometry modification combined with end plate addition significantly improves turbine performance. Model C exhibited the best performance, achieving a maximum mechanical power of 0.36 W and a maximum torque of 0.0135 Nm at a wind speed of 5.0 m/s. Furthermore, Model C attained the highest power coefficient (Cp), with a maximum Cp of 0.16 at a wind speed of 3.0 m/s, indicating the most optimal aerodynamic efficiency. In conclusion, the combination of a helical blade and an end plate effectively reduces tip losses while maximizing energy conversion. This design is therefore strongly recommended for the development of micro-scale wind power generation in regions characterized by low wind speeds.